Heritable Gene Knockout in Caenorhabditis elegans by Direct Injection of Cas9–sgRNA Ribonucleoproteins - Cho, Seung Woo; Lee, Jihyun; Carroll, Dana; Kim, Jin-Soo; Lee, Junho (Genetics (Austin), 2013)
We present a novel method of targeted gene disruption that involves direct injection of recombinant Cas9 protein complexed with guide RNA into the gonad of the nematode Caenorhabditis elegans. Biallelic mutants were recovered among the F1 progeny, demonstrating the high efficiency of this method.